Metodicheskie osnovy sovershenstvovaniya sportvnykh uprazhnenii posredstvom optimizatsii ikh kharakteristik - Ippolitov, Yu.; Cheburaev, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The aim of this paper was to represent the new method of the sports exercises` improvement with a help of their characteristics` optimization. The authors describe the algorithm of the exercises` carry out improvement. The given method can be used to improve the results of various distances running, ski and bicycle races and other sports locomotions.